2009
DOI: 10.1021/ma802180f
|View full text |Cite
|
Sign up to set email alerts
|

Study of Thickness Dependent Density in Ultrathin Water Soluble Polymer Films

Abstract: Density of the polyacrylamide ultrathin films has been studied using X-ray reflectivity technique. Two sources (one powder and another aqueous solution) of polyacrylamide were used to prepare spin coated films on silicon substrate. Light scattering measurements show that the polymer chains were unentangled in a concentrated (4 mg/ml) as well as in a dilute (2 mg/ml) solution prepared from the powder, whereas the solution (4 mg/ml) prepared by diluting the solution source shows entangled chain morphology. Three… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…This initial "slow" reduction of thickness may be attributed to the compaction of the films due to larger mobility of the polymer chains above the glass transition temperature (165 o C for polyacrylamide) as observed earlier. 23,27 The increase of rate of thickness reduction above 210 o C indicates possibility of additional chemical changes in the film. In the cooling cycle there was a small reduction of the film thickness at the initial stage probably due to the inertial effects of the slow chain dynamics, thereafter the thickness of the film remains constant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This initial "slow" reduction of thickness may be attributed to the compaction of the films due to larger mobility of the polymer chains above the glass transition temperature (165 o C for polyacrylamide) as observed earlier. 23,27 The increase of rate of thickness reduction above 210 o C indicates possibility of additional chemical changes in the film. In the cooling cycle there was a small reduction of the film thickness at the initial stage probably due to the inertial effects of the slow chain dynamics, thereafter the thickness of the film remains constant.…”
Section: Resultsmentioning
confidence: 99%
“…In figure 6 we have plotted the average electron density for all the films before and after annealing as a function of spinning speed of their preparation. 23 In table 1 percentage increase of density values with respect to dry films are tabulated for all the films. The reduction of film thickness for various films was between 8.4 to 16.7% and the increase of density ranges from 0-12.6% (compared to those of the dry films) without having any systematic dependence between the two.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A schematic regarding this is shown in Figure 3.This renders lower entanglement of the polymer chains thereby leading to a higher order of orientation of the polymer chains because of the stronger polymer-solvent, polymer-polymer, and polymer-substrate interactions. Highly ordered polymer chains result in a higher density of the polymer chains leading to an enhancement in the refractive index [67][68][69] .…”
Section: Figurementioning
confidence: 99%
“…Polymer films represent one of the most used classes of soft matter with applications ranging from functional coatings and sensors to separation membranes and organic electronics. Along with the chemical composition, the conformations of macromolecular chains determine the properties of polymer films such as glass transition temperature ( T g ) [1,2], electron densities [3], wetting [4,5], rheology [6], solvent absorption, and swelling dynamics [7,8]. Extensive research has revealed that characteristics of thin polymer films strongly deviate from the properties these polymers exhibit in bulk [9].…”
Section: Introductionmentioning
confidence: 99%